2008
DOI: 10.1080/09593330802296173
|View full text |Cite
|
Sign up to set email alerts
|

Municipal Wastewater Treatment in an Anaerobic Digester‐constructed Wetland System

Abstract: An experimental plant was constituted for an upflow anaerobic sludge blanket (UASB) reactor with an active volume of 25.5 m3 and two horizontal constructed wetlands of 75 m2 each. The first wetland was a superficial flow (SF) system and the second a subsurface flow (SSF) system. The UASB reactor was fed with 60-73 m3 d(-1) of raw domestic wastewater from the municipal treatment plant (MTP) of the city of Santiago de Compostela. Part of the effluent from the UASB reactor (15 m3 d(-1)) passed through the SF wetl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Since anaerobic digestion takes place in the septic tank, little removal of nitrogen and phosphorus can be expected [22,23]. The results of this study indicated that the removal of phosphorus at HRTs of 72, 48 and 24 h were 29.3%, 26.9% and 25.6%, respectively.…”
Section: Performance Of the Conventional Septic Tankmentioning
confidence: 85%
“…Since anaerobic digestion takes place in the septic tank, little removal of nitrogen and phosphorus can be expected [22,23]. The results of this study indicated that the removal of phosphorus at HRTs of 72, 48 and 24 h were 29.3%, 26.9% and 25.6%, respectively.…”
Section: Performance Of the Conventional Septic Tankmentioning
confidence: 85%
“…Researchers have reported lower efficiency of UASB reactor during the treatment of low strength complex wastewaters due to the lower removal of suspended organic matter [28][29][30][31].…”
Section: Blanket (Muasb) Reactorsmentioning
confidence: 99%
“…Mixing can facilitate the release of produced gas in bioreactor. Therefore, higher turbulence in MUASB may help gas bubble to release from granular surface [27].Researchers have reported lower efficiency of UASB reactor during the treatment of low strength complex wastewaters due to the lower removal of suspended organic matter [28][29][30][31].Therefore, the presence of TSS possibly reduces the efficiency of UASB reactor during the treatment of municipal sewage in this study. Low influent COD results in low gas production, thereby decreasing the collision opportunity of influent solids with sludge biomass.…”
mentioning
confidence: 96%
“…For the case study, we selected an Upflow Anaerobic Sludge Blanket (UASB) combined with Vertical Flow Constructed Wetlands (VFCW). The selected treatment train is a low-cost alternative for rural sanitation that allows reuse practices (de Sousa et al 2001;El-Khateeb & El-Gohary 2003;Halalsheh et al 2008;Ruiz et al 2008). Concerning sewage sludge management, we evaluated an on-site sludge treatment facility using Sludge Drying Reed Beds (SDRBs) (Nielsen & Willoughby 2005).…”
Section: Selected Technologies For Wastewater and Sewage Sludge Treatmentioning
confidence: 99%